ARR, Hinc Quo?. Issue 2 (2nd July 2016) - Kuczera, George; Babister, Mark; Retallick, Monique; Adam, Melissa
Abstract: With the release of the 2016 edition of Australian Rainfall and Runoff (ARR), this paper asks the question, from here to where? It focuses on the core business of ARR, which is the estimation of flood quantiles, and assesses the accuracy of the two main approaches: flood frequency (FF) and joint probability (JP), of which the design storm (DS) approach is the simplest. The sources of uncertainty affecting FF and JP quantile estimation are dissected, and it is argued that the prevailing wisdom of the DS approach being more accurate than FF is questionable. A comparative error analysis of quantile estimates derived using gauged and regional application of FF and DS methods is presented using data from twenty-six well-gauged catchments. While FF tended to have better skill than DS methods, the skill levels were low. In the worst case, the regional DS method produced 90% probability limits for the 1 in 100 AEP quantile of 35% to 290%! These findings bring little comfort and highlight the fact there is much "unfinished business". Two strategies are offered as a way forward: the first to reduce quantile uncertainty and the second to communicate and manage the large uncertainty inherent in quantile estimation.